Unifying Themes in Complex Systems VII Proceedings of the Seventh International Conference on Complex Systems - Minai, Ali A.; Braha, Dan.; Bar-Yam, Yaneer; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The International Conference on Complex Systems (ICCS) creates a unique atmosphere for scientists of all fields, engineers, physicians, executives, and a host of other professionals to explore common themes and applications of complex system science. With this new volume, Unifying Themes in Complex Systems continues to build common ground between the wide-ranging domains of complex system science.
Complex Adaptive System-Based Decision Support for Enabling Organizationoal Change -- Multi-Level Behaviours iin Agent-Based Simulation: Colonic Crypt Cell Populations -- Developing a Complex Approach to Health Phenomena -- Virtual Spring-Based 3D Multi-Agent Group Coordinations -- Exploration for Agents With Different Personalities in Unknown Environments -- The Self-Made Puzzle -- the Necessity of Conceptual Skill Enhancement to Address Philosophical Challenges of New Science -- Evolutionary Perspective on Collective Decision Making -- Desrupting Terrorist Networks - A Dynamic Fitness Landscape Approach -- The World as Evolving Information -- Inferring Diversity: Life After Shannon -- Life at the "Edge of Chaos" in a Genetic Model -- The Effects of Complexity on the Product-Service Shift -- Rapid Software Evolution -- Structureal Changes and Adaption of Algal Population under Different Regimes of Toxic Exposure -- Modularity and Self-Organized Functional Structures n the Brain -- An Introduction to Complex-System Engineering -- Statistical Properties of Agent-Based Market Area Model- Complexity and the Social Sciences: Insights from Complementary Theoretical Perspectives -- Agent-Based Model of Livestock Movements. Random Graph Models of Comunication Toplogies. -Using RDF to Model the Structure and Process of Systems -- How Do Agens Represent? -- A CAS for Finding the Best Strategy for Prisoner's Dilemma. - A Complex Systems Approach to the Designa Evaluation of Holistic Security Ecosystems -- Exploring Watts' Cascade Boundary -- Index of Authors.
Keywords: Physics; Artificial intelligence; Engineering; Physics; Statistical Physics, Dynamical Systems and Complexity; Complexity; Artificial Intelligence (incl. Robotics).